O plano de gestão escolar de Santa Catarina : gestão democrática na educação? - Ramos, Dhian Rafael Barbosa (2025)
This dissertation analyzes the school management model implemented in the state of Santa Catarina since 2013 and uses field research in two state schools located in the interior of the state. The methodology is quantitative and qualitative, and the technical procedures include documentary, bibliographic, and questionnaire-based field research. The questionnaire was administered to teachers and students at two state schools in the municipality of Anita Garibaldi, Santa Catarina. The research question is formulated as follows: how does the implementation of the school management plan contribute to Democratic Management movements? The general objective of this research is to analyze the implementation of school management plans within Democratic Management movements. The specific objectives of this study are to: identify public education policies and their links to systems and schools, as well as the policy cycle; theoretically analyze the pedagogical assumptions and representations of democratic management; identify the role of the school principal and the implementation of the school management plan; understand the development steps of School Management Plans implemented in the state units of Santa Catarina and their evaluation. The main theoretical frameworks adopted are Arroyo (1979), Ball and Bowee (1992), Bornedave (1994), Veiga (1998), Libâneo (2001), Souza (2009), Paro (2018), and Vieira (2011). The data collection instrument was a questionnaire (Google Forms) addressed to second-year high school students and teachers in the schools studied. The data were analyzed by 63 students, corresponding to 70.89%, and 20 teachers, equivalent to 80.64% of those who responded to the research problem. The conclusive findings point to significant progress and advancement in democratic management through the implementation of the Management Plan, as it ensures community participation, respects the collective, and enables democratic management with access to discussions and decision-making. It is common to see the execution of prior planning by the plan's proponent, which, due to the participation of the school community, can be evaluated and changed during the Plan's validity. However, it is important to note that the Plan, although it contains elements of a culture of democratic management, could only effectively ensure this practice if supported by a State Policy—and not just a government policy—considering that democratic management must prioritize the defense of public schools.